Scottish Rite Freemasonry building. - Gordon, John C. (photographer):::Creator::::::::::::
Photograph shows the Scottish Rite Freemasonry building. Inscribed above the entrance of the building is "Temple of the ancient and accepted Scottish Rite of Freemasonry dedicated to the worship of God, to the service of the people, to liberty, equality and fraternity." This building is situated at 196 North. 3rd Street, San Jose, CA.